ALMAN İNTERNET GAZETELERİNDE ALEVİLERİN TEMSİLİ ve TAKDİMİ (2007-2023) - İlhan KARACA (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi, 2023)
In the study, the media representation of Alevis, which constitutes a subculture form within the Turkish culture in Germany, has been researched. Acting on the assumption that representation is a construction process, in this study, an answer was sought to the question of through which other set of values and beliefs the mass media present Alevis -who they are and what they believe are hardly known both in the realm of academic literature and to the German public. The empirical data of this research, which is a document analysis, were collected from online newspapers, one of the most important information tools of the new media today, and analyzed according to the grounded theory method. A total of 35 articles from 17 different newspapers were subjected to this analysis. The results show that Alevis were noticed by the media with the enactment of the German integration policies, which turned into a debate on Islam towards the end of the 90s, and these policies formed the socio-cultural context of the media representation of Alevis. Although Germany has made considerable progress with these policies, which envisage their one-way integration without due regard to the basic cultural rights of immigrants of Muslim origin, it has fallen behind its ideals of being an open and liberal society. It resorted to the strategy of rebuilding these ideals through Alevism, which it identified as an “alternative Islam” to mainstream Islam. In this context, this study researching the media representation of Alevis concluded that the mass media instrumentalized Alevism by defining it in a way that would serve the interests of German integration policies.